Acculturation Between Islam with Local Culture in Muslim Minority: The Experience from Pakpak-Dairi, North Sumatra - Maimanah Angkat; Katimin Katimin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
This article discusses of acculturation between Islam and local culture in the Pakpak-Dairi community. The contact between the two cultural elements does not negate each other but is accommodative. This paper shows that Pakpak Dairi’s current culture results from long acculturation between cultures, namely ancestral traditions, Hindu-Buddhist, and Christian. The research findings confirm that the politics of Islamic acculturation is reflected in various traditional ceremonies and other cultural expressions. Religious and traditional leaders play a role as agents in the acculturation process received of Islam. This process also contributes to the realization of social harmony in the Pakpak-Dairi community